2005
DOI: 10.1038/sj.mp.4001774
|View full text |Cite
|
Sign up to set email alerts
|

Why do young women smoke? I. Direct and interactive effects of environment, psychological characteristics and nicotinic cholinergic receptor genes

Abstract: Despite the health hazards, cigarette smoking is disproportionately frequent among young women. A significant contribution of genetic factors to smoking phenotypes is well established. Efforts to identify susceptibility genes do not generally take into account possible interaction with environment, life experience and psychological characteristics. We recruited 501 female Israeli students aged 20-30 years, obtained comprehensive background data and details of cigarette smoking and administered a battery of psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
136
0
4

Year Published

2007
2007
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(147 citation statements)
references
References 66 publications
7
136
0
4
Order By: Relevance
“…Mice with the A529 variant exhibited enhanced sensitivity to the effects of nicotine and increased consumption of nicotine, compared to mice with the T529 variant of the α4 nAChR subunit (Dobelis et al, 2002;Butt et al, 2003;Butt et al, 2005). In human research, polymorphisms in Chrna4 have been identified that may be protective against nicotine dependence (Feng et al, 2004;Li et al, 2005), and some evidence suggests that polymorphisms in the β2 nAChR subunit gene (Chrnb2) may be associated with smoking initiation (Greenbaum et al, 2006but see Lueders et al, 2002Silverman et al, 2000). Although polymorphisms in Chrna4 and Chrnb2 have been implicated in nicotine addiction, the effects of polymorphisms of Chrna4 or Chrnb2 on nicotine withdrawal remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with the A529 variant exhibited enhanced sensitivity to the effects of nicotine and increased consumption of nicotine, compared to mice with the T529 variant of the α4 nAChR subunit (Dobelis et al, 2002;Butt et al, 2003;Butt et al, 2005). In human research, polymorphisms in Chrna4 have been identified that may be protective against nicotine dependence (Feng et al, 2004;Li et al, 2005), and some evidence suggests that polymorphisms in the β2 nAChR subunit gene (Chrnb2) may be associated with smoking initiation (Greenbaum et al, 2006but see Lueders et al, 2002Silverman et al, 2000). Although polymorphisms in Chrna4 and Chrnb2 have been implicated in nicotine addiction, the effects of polymorphisms of Chrna4 or Chrnb2 on nicotine withdrawal remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…134,140 Several studies failed to find any associations between genetic variation in CHRNB2, which encodes the b 2 subunit, with smoking initiation or ND. 137,138,141,142 However, Greenbaum et al 139 found that rs2072660, which had been examined in other studies with negative results, and its haplotypes had a nominally significant protective effect against smoking initiation. SNPs in CHRNA7 (rs1909884), CHRNA9 (rs4861065) and CHRNB3 (rs9298629) also appeared protective against high levels of ND (FTQ X6), although none remained significant after correction for multiple testing.…”
Section: Cholinergic Receptorsmentioning
confidence: 98%
“…A study in Chinese men found an association of two synonymous SNPs in exon 5 (rs1044396 and rs1044397) with a lower risk of ND, 137 but these findings were not confirmed in either male or female subjects of other ethnicities. 138,139 In an analysis of six SNPs (including rs1044396), only one (rs2236196), and its…”
Section: Cholinergic Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a design that compares users (both dependent cases and non-dependent users) with abstainers addresses genetic influences that effect both initiation and dependence. A few studies involving nicotine have used this three-subject group design Greenbaum et al, 2006;Lerer et al, 2006;Sullivan et al, 2001a;Sullivan et al, 2001b;Zhang et al, 2006) and separately assessed genetic effects for initiation from those for dependence. These studies, conducted in the U.S. and Israel, also supported the two-stage model, providing further evidence of the value of such a design in genetic association studies of illicit substances.…”
Section: Implications Of This Studymentioning
confidence: 99%